Beyond the digital swarm? Byung-Chul Han's critical media pessismism. - Suetzl, Wolfgang (AoIR Selected Papers of Internet Research, 2017)
The Korean-German philosopher Byung-Chul Han has established a reputation as a pop philosopher and apocalyptic of digital media. This paper examines the recurring themes of “positivity,” “transparency” and “digital swarm” in terms of their potential to contribute to a critical theory of digital networks. It identifies parts of Han’s thought that can do this, centered on his critique of positivity, which applies to social media communication and neo-positivist research cultures media studies. It suggests caution with Han’s implicit nostalgia of less alienated pre-digital social reality. While Han’s reputation of a media apocalyptic is mostly grounded in three of his most recent books (which are also the ones available in English translation), earlier works, concerned with an analysis of power and with a dialogue between western poststructuralism and elements of east Asian philosophical traditions suited to help overcome a Eurocentrism in media studies.